Infantile Spasms in Children With Down Syndrome: Identification and Treatment Response. (January 2019) - Daniels, Dee; Knupp, Kelly; Benke, Tim; Wolter-Warmerdam, Kristine; Moran, Maura; Hickey, Fran
Objectives. To evaluate infantile spasms in children with Down syndrome including assessment of efficacy of treatments, presence of treatment lag, and to identify risk factors that may predict the occurrence of infantile spasms in this population. Methods. Medical charts, electroencephalograms, and brain magnetic resonance images were evaluated in 37 children treated for infantile spasms at a single institution from 2005 to 2015. Results. Mean age at diagnosis was 9.16 months, with an average 1.38-month lag from spasms onset to start of medication. Prevalence of heart defects and pulmonary hypertension were significantly higher in those with infantile spams compared with those without. Eighty-one percent receiving adrenocorticotropic hormone as initial treatment experienced remission within 2 weeks, 94.1% had remission at 3 months compared with 18.8% at 2 weeks and 35.3% at 3 months for other first-line treatments. Type of treatment was the only predictor of good outcome. Conclusions. Results stress the importance of early recognition and adrenocorticotropic hormone treatment for this seizure disorder in children with Down syndrome.